A real-life study on the impact of direct-acting antivirals in the treatment of chronic hepatitis C in liver transplant recipients at two university centers in Northeastern Brazil - Silva, Isabella Patrícia Lima (2021)
The efficacy of direct-acting antivirals (DAAs) in the treatment of chronic hepatitis C (CHC) in liver transplant recipients is poorly understood, and several factors, including immunosuppression, drug interactions, elevated viraemia, and intolerance to ribavirin (RBV), can reduce cure rates. We conducted a real-life study on liver transplant recipients with CHC treated with a combination of sofosbuvir (SOF) and daclatasvir (DCV) or simeprevir (SIM), with or without RBV, followed-up for 12 to 24 weeks. The treatment effectiveness was assessed by determining the sustained virological response (SVR) rates at 12 or 24 weeks after the treatment cessation. Eighty-four patients were evaluated, with a mean age of 63.4 ± 7.4 years, HCV genotype 1 being the most prevalent (63.1%). Nineteen patients (22.7%) had mild fibrosis (METAVIR < F2) and 41 (48.8%) significant fibrosis (METAVIR ≥ F2). The average time between liver transplantation and the start of treatment was 4 years (2.1-6.6 years). The SOF + DCV regimen was used in 58 patients (69%). RBV in combination with DAAs was used in seven patients (8.3%). SVR was achieved in 82 patients (97.6%), and few relevant adverse events could be attributed to DAA therapy, including a patient who stopped treatment due to a headache. There was a significant reduction in ALT, AST, GGT and FA levels, or the APRI index after 4 weeks of treatment, which remained until 12/24 weeks post-treatment. DAA treatment of CHC in liver-transplanted patients achieved a high SVR rate and resulted in the normalization of serum levels of liver enzymes.